DEVELOPMENT AND IDENTIFICATION OF COMBINED PAIN ASPECTS IN LOW BACK PAIN: A REVIEW AND ANALYSIS - Friyan Maulana, Ilmi (Journals of Ners Community, 2023)
Lower back pain is a commonly occurring health issue and has a significant impact on the financial well-being of patients and their families. In the context of pathophysiology, pain can be classified into three main types: nociceptive pain, neuropathic pain, and central sensitization. Although about 85% of lower back pain cases lack a clear primary cause, the impact of this pain is palpable for patients. With the advancement of medical knowledge, the concept of Mixed Pain emerges as an entity where pain arises from a combination of several pathophysiological factors. However, the term "mixed pain" does not yet have a widely accepted formal definition, limiting its usage. Therefore, further investigation is needed regarding clinical indicators related to mixed pain. This is crucial for enhancing the process of identifying the type of pain more accurately, enabling a more rational selection of therapies, and ultimately improving the quality of life for patients experiencing lower back pain. Further research in this field could lead to the development of clearer guidelines for clinically identifying mixed pain, considering various elements of involved pathophysiology. Moreover, a better understanding of mixed pain can facilitate the development of more targeted therapies, with a more personalized and effective approach. Through these efforts, it is hoped that individuals with lower back pain will experience a significant improvement in their quality of life and a reduction in the financial impact caused by this condition, both for patients and their families.